Electricity generation in simulated benthic microbial fuel cell with conductive polyaniline-polypyrole composite hydrogel anode. (January 2022) - Xu, Haitao; Du, Yanan; Chen, Ye; Wen, Qing; Lin, Cunguo; Zheng, Jiyong; Qiu, Zhenghui
Abstract: As a sustainable and eco-friendly technology, the benthic microbial fuel cell (BMFC) has been emerged as alternative and potential approach to recover electrical energy by microorganisms, but lower power density and poor long-term life hinder their practical application. Modification of anodic materials is an efficient strategy to solve this problem. Here, a conductive and biocompatible hydrogel electrode, polyaniline-polypyrole-CNTs-Fe3 O4 (PANI-PPy-CNTs-Fe3 O4 ) is prepared and applied as anode in a simulated BMFC. The maximum power density of the BMFC with PANI-PPy-CNTs-Fe3 O4 hydrogel anode (5901.49 mW/m 3 ) is 1.33, 2.15 and 2.06 times higher than that of PANI-PPy (4413.03 mW/m 3 ), PANI and PPy anodes (2737.12 and 2859.53 mW/m 3 ), respectively. The charge transfer resistance of quaternary hydrogel bioanode in BMFC (3.922 Ω) is much lower than that of the PANI (8.682 Ω), PPy (8.262 Ω) and PANI-PPy (5.772 Ω) hydrogel bioanodes. Moreover, the extracellular electron transfer ability is also enhanced on the composite hydrogel anode, which also exhibits the high biomass. High-throughput sequencing technology indicates that the synergistic effect of bacteria on the quaternary hydrogel made full use of organic matter as available fuel to enable a high electricity-generation anode. Such foregoing mainly ascribed to the composite hydrogel keep the high biocompatibility from components, while the addition of CNTs and Fe3 O4 dramatically decreases the internal resistance and provides more electrochemical active surface area on basis of macroporous 3D hydrogel structure. This work explores the composite hydrogel used as anodes to construct high-performance BMFC and provides significant information for the applications of actual BMFCs in the future. Highlights : A conductive and biocompatible hydrogel, PANI-PPy-CNTs-Fe3O4, was prepared. The hydrogel electrode was applied as anode in a simulated BMFC for the first time. The hydrogel composite exhibited more electrochemical active surface area. The power density of BMFC with modified anode increased by 115%. The great performance was due to the synergy of each component in hydrogel.